2018
DOI: 10.5205/1981-8963-v12i6a230633p1751-1762-2018
|View full text |Cite
|
Sign up to set email alerts
|

Contribuições da simulação para estudantes de graduação em enfermagem

Abstract: RESUMOObjetivo: identificar as contribuições da simulação para estudantes de graduação em enfermagem. Método: revisão de escopo com a questão norteadora: “Quais as contribuições da simulação para estudantes de graduação em enfermagem?” Foram consultadas, durante o mês de maio de 2017, a biblioteca: Scielo, as bases de dados Medline e LILACS, utilizando-se os descritores: “aprendizagem”, “educação”, “simulação”, “simulação de paciente”, “treinamento por simulação” e “enfermagem”, posteriormente, duas revisoras … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
11

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 4 publications
0
7
0
11
Order By: Relevance
“…Studies show that, when simulation is well-planned and meaningful to its participants, it raises their level of confidence and self-efficacy, reinforces knowledge, improves self-care skills, communication and interpersonal relations, developing critical thinking and clinical judgment while promoting empathy and reflection on one's own actions (20,29) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies show that, when simulation is well-planned and meaningful to its participants, it raises their level of confidence and self-efficacy, reinforces knowledge, improves self-care skills, communication and interpersonal relations, developing critical thinking and clinical judgment while promoting empathy and reflection on one's own actions (20,29) .…”
Section: Discussionmentioning
confidence: 99%
“…Although simulation is mostly developed with nursing students (6,20,26) , this instrument was developed for simulation with nurses in an educational institution. It may nonetheless apply to nursing students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of this study demonstrated that there was an improvement in learning when we evaluated the overall performance of the intervention group, submitted to the simulation compared to the control group. Corroborating this result, the literature (19) states that simulation favors critical and reflective learning, contributing positively to the development of skills necessary for the training of nursing students.…”
Section: Discussionmentioning
confidence: 89%
“…Literature reveals that simulation training in mock panels, used as a teaching method, contributes for the learning and the didactic innovation of Nursing students. That improves learning, since the confidence of the students and their ability to communicate improve, and they develop critical thinking, integrating theory and practice (5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%